Prawie takie jak dziś? Uwagi o Norwidowskich użyciach wyrażenia „prawie” - Chojak, Jolanta (Idiolekty, 2025)
This study looks into Norwid’s use of the lexeme prawie (almost), analyzing its occurrences within his complete corpus. The analysis reveals a predominant adherence to contemporary patterns of usage and collocational rules, though no examples of numeral-related applications are present. In these contexts, prawie acts as a marker of approximation and functions as a metapredicative operator: it provides a structural position for semantically defined expressions. Although it does not bear a non-contrastive phrasal accent, it is an integral part of sentence structure. Additionally, Norwid’s texts feature instances where prawie assumes a metatextual role. As a metatextual operator, it imposes no semantic or formal restrictions on co-occurring expressions. Instead, it operates as a reflective commentary on the utterance as a complete communicative act. This metatextual use positions prawie outside traditional sentence syntax, embedding it within the thematic/rhematic structure. Such occurrences justify its classification as an epistemic particle. The corpus also includes a few isolated occurrences of prawie used as a standard adverb with non-contrastive phrasal accents in object-level expressions. However, these examples do not signify epistemic states; rather, they function as subjective adverbs with the specific meaning “in a manner befitting righteous individuals”.